Landscape dynamics in southern Finland during the Iron Age and the Early Modern Era — Pollen-based landscape reconstruction (LRA), macrofossil and historical data from Western Uusimaa. (April 2017) - Alenius, Teija; Haggrén, Georg; Koivisto, Satu; Vanhanen, Santeri; Sugita, Shinya
Highlights: Pollen-inferred quantitative reconstruction of past vegetation cover on the coastal mainland and in the archipelago of southern Finland are presented on a regional spatial scale using the REVEALS model and on local spatial scales using the LOVE model. The pollen data is complemented by data on charred macrofossil plant remains of cultivated species, which has not been compiled together from the area of western Uusimaa earlier. The focus of the study is from the Iron Age (500 BCE) to modern times (1550 CE). Quantitative estimates of regional vegetation obtained with REVEALS showed that from 650 BCE until 950 CE, forests dominate the landscape. The meadow/grassland vegetation increased significantly from 1150 CE onwards showing how the diversified semi-natural landscape and the cultural landscape visible in the early 20th century were built up already in the Middle Ages.